2015
DOI: 10.1111/jfpp.12669
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Activity of Tea Polyphenols on Biofilm Development of Shewanella putrefaciens

Abstract: Shewanella putrefaciens has been identified as the main specific spoilage organism during iced storage of marine fish. In this study, the inhibitory effects of tea polyphenol (TP) against biofilms of Sh. putrefaciens were evaluated. The addition of TP at the initial time exhibited the strongest biofilm inhibitory effect, while applying after 10 h or later did not show significant inhibitory effect. TP significantly inhibited the initial cell attachment on stainless steel in a concentration‐dependent manner. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The results of antimicrobial activity (Table 1) indicated that nitrite effectively inhibited the growth of C. perfringens, which was consistent with the previous reports [10]. The tea polyphenols, a new natural antibacterial agent, could significantly inhibit the growth of Escherichia coli, Klebsiella pneumoniae, Shewanella putrefaciens, and other microbes [35]; however, they have little inhibitory effect on C. perfringens. It might be because C. perfringens itself differs from other bacteria in certain ways.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results of antimicrobial activity (Table 1) indicated that nitrite effectively inhibited the growth of C. perfringens, which was consistent with the previous reports [10]. The tea polyphenols, a new natural antibacterial agent, could significantly inhibit the growth of Escherichia coli, Klebsiella pneumoniae, Shewanella putrefaciens, and other microbes [35]; however, they have little inhibitory effect on C. perfringens. It might be because C. perfringens itself differs from other bacteria in certain ways.…”
Section: Discussionsupporting
confidence: 89%
“…Spores released more protein throughout the entire germination process. The survival rate of C. perfringens spores was greatly decreased by tea polyphenols; it could be primarily attributed to the inactivation of enzymes and disruption of cell metabolism after these substances had penetrated into spores after germination [35]. At the same time, during the spore germination process, tea polyphenols might infiltrate into the spore and act on the spore genetic material, which also increases the possibility that the spore could not grow [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Mature biofilms are usually stubborn and difficult to be eliminated, which makes it extremely meaningful to inhibit the formation of bacterial biofilms at the origin. Several studies have reported that TP can prevent the biofilm formations of spoilage bacteria ( Shewanella putrefaciens ) and foodborne pathogen ( Vibrio mimicus ) by extracellular matrix secretion, motility and quorum sensing inhibitions (Zhang et al ., 2016; Li et al ., 2020). However, the reports about the effects and mechanisms of KA or KA‐TP on bacterial biofilm inhibition were limited, and only one study has stated that KA at sub‐MICs exhibited the anti‐biofilm formation activities against five common foodborne pathogens (Wu et al ., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…All the mixtures were transferred to 96‐well plates, and each treatment was repeated for six wells. After incubation at 37 °C for 2 days, the biofilm formation was determined by measuring OD 490 nm of each well after CV staining (Zhang et al ., 2016).…”
Section: Methodsmentioning
confidence: 99%
“…It is important to say that antimicrobial and anti-biofilm formation properties must be distinguished. It was previously described that tea polyphenols did not affect planktonic growth of Shewanella putrefaciens but were more effective in the inhibition of their initial attachment and the metabolic activity of the biofilm [116]. On the contrary, the most potent compounds towards planktonic cells were not always the most potent towards biofilm [117].…”
Section: Natural Compounds As Biofilm Inhibitorsmentioning
confidence: 88%